Postnatal penicillin prophylaxis of early-onset group B streptococcal infection in term newborns. A preliminary study - Stillova, Lucia; Strechova, Zuzana; Matasova, Katarina; Kolarovszka, Hana; Bodova, Kristina; Stilla, Juraj; Zibolen, Mirko (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Early-onset group B Streptococcal disease (EOGBSD) is a serious but preventable neonatal infection. Maternal intrapartum antibiotic prophylaxis (IAP) does not prevent all cases of the disease. Management of asymptomatic neonates of GBS colonized mothers is problematic. AIMS: The objective of this prospective study was to determine whether administration of intramuscular penicillin at birth to a strictly defined group of term newborns of GBS colonized mothers is an effective and safe method to prevent EOGBSD. METHODS: A protocol for management of full-term infants born to GBS colonized mothers was created. Either an abnormality of blood count or presence of more than one obstetric risk factor were chosen as the indication criteria for administering postnatal antibiotic prophylaxis (PAP). RESULTS: The study sample consists of 250 newborns (11.5% of all term infants). PAP was administered in 39 cases. Indication criteria included leucocytosis in 37 cases, leucopenia in 1 case and obstetric risk factors in 1 case. There was no case of clinically manifest infection, and no case of sepsis either suspect or proven. CONCLUSIONS: The authors suggest that the strategy of selective PAP using penicillin, may be an effective and safe method in order to reduce morbidity and mortality from streptococcal infections. They recommend a combination of IAP and selective PAP.
Keywords: streptokokové infekce; novorozenec; Infant, Newborn; antibiotická profylaxe; rizikové faktory; Injections, Intramuscular; Penicillins; Streptococcal Infections; peniciliny; Antibiotic Prophylaxis; Humans; injekce intramuskulární; lidé; Streptococcus agalactiae; Risk Factors